Lermontov’s Sketch “Russia Has no Past...” in Context of “Eastern Question”: to Problem of Poet’s Artistic Historiosophy - I. A. Kiseleva; K. А. Potashova (Научный диалог, 2022)
The subject of the study was the content of Lermontov’s autograph “Russia has no past...” from the “Notebook donated by V. F. Odoevsky” in the aspect of the poet’s historical views. The purpose of the article is connected with the establishment of the historical and cultural genesis of the text and the clarification of its meaning in the context of Lermontov’s work, Russian-Caucasian interaction, as well as the historiosophical concepts of the first third of the 19th century. The research methodology is connected with textological, historical-genetic, cultural-historical, comparative-historical approaches to text analysis. The specific tools are the description of the autograph, as well as the preparation of a textological passport that reflects the technical aspects of the handwritten text. Lermontov’s note is presented in the context of a dialogue with contemporaries and folklore tradition. The historical and literary context of Lermontov’s note, its allusions to the facts of sociohistorical thought and images of Russian literature emphasize Lermontov’s patriotism. As a result of the study, Lermontov’s protoPan-Slavic concept was reconstructed, which correlates with ideas about the ways of Russia’s development as a great power. The conclusion of the study was the understanding of Lermontov’s sketch “Russia has no past...” as an emanation of the poet’s reflections on relations between Russia and the Caucasus in the aspect of the “Eastern question”.